A Study on the Scope of Distance Education: Challenges and Solutions in India's Open and Distance Learning System (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Open and Distance Learning arrangement of training had developed massively around the globe during the 1960s. It was likewise begun in India as correspondence or separation learning by some conventional colleges, for example, Delhi University (since 1962). The framework was energized in the mid 1980s, when the Union Government passed a bill to build up a focal college for previous Prime Minister Indira Gandhi in 1985. The Distance Education Council (DEC) was likewise set up under a similar Act to arrange separation learning between the organization and to keep up the norm of training at the degree of India all in all. From that point forward, the ODL framework has been doing admirably under the administration of the Central Open University IGNOU. In a creating nation like India, there are numerous genuine issues with the execution of government strategy. In any case, the arrangement of issues and the revelation of plausible arrangements are additionally done consistently. This paper manages the advantages, victories, disadvantages and a few proposals for defeating the current issues looked by the ODL framework in India.